Les « étrangers » du roi - Thomas Glesener (Mélanges de la Casa de Velázquez, 2005)
This article inquires into the changes that occurred between the 17th and 18th centuries as regards the importance and the role of «nations» in the military household of the Kings of Spain. The militarisation of the guard corps marked a break with the representative function of the « nations » at Court. From that time on the criterion governing resort to the King of Spain’s European vassals was one of military efficacy. However, within the French milieu surrounding the King of Spain, there were two opposing views. The first, espoused by Louville, called for a guard composed entirely of persons not native to the kingdom, who should act as guarantors of the royal power. The Princess des Ursines, Jean Orry and Abbott d’Estrées defended the second, which called for the guard corps to be opened to the Spanish elites. The latter view eventually prevailed, and the institution became an instrument of integration.